Pre-harvest sugarcane burning: Determination of emission factors through laboratory measurements - França, Daniela de Azeredo; Longo, Karla Maria; Neto, Turibio Gomes Soares; Santos, José Carlos; Freitas, Saulo R.; Rudorff, Bernardo F. T.; Cortez, Ely Vieira; Anselmo, Edson; Carvalho Jr., João Andrade [UNESP] (MDPI, 2012)
Sugarcane is an important crop for the Brazilian economy and roughly 50% of its production is used to produce ethanol. However, the common practice of pre-harvest burning of sugarcane straw emits particulate material, greenhouse gases, and tropospheric ozone precursors to the atmosphere. Even with policies to eliminate the practice of pre-harvest sugarcane burning in the near future, there is still significant environmental damage. Thus, the generation of reliable inventories of emissions due to this activity is crucial in order to assess their environmental impact. Nevertheless, the official Brazilian emissions inventory does not presently include the contribution from pre-harvest sugarcane burning. In this context, this work aims to determine sugarcane straw burning emission factors for some trace gases and particulate material smaller than 2.5μm in the laboratory. Excess mixing ratios for CO2, CO, NOX, UHC (unburned hydrocarbons), and PM2.5 were measured, allowing the estimation of their respective emission factors. Average estimated values for emission factors (g kg-1 of burned dry biomass) were 1,303 ± 218 for CO2, 65 ± 14 for CO, 1.5 ± 0.4 for NOX, 16 ± 6 for UHC, and 2.6 ± 1.6 for PM2.5. These emission factors can be used to generate more realistic emission inventories and therefore improve the results of air quality models. © 2012 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: CO; CO2; Emission factors; Experimental fires; Hydrocarbons; NOX; PM2.5; Sugarcane burning; Air quality models; Burning emissions; Dry biomass; Emission inventories; Emissions inventory; Environmental damage; Laboratory measurements; Mixing ratios; Particulate materials; Sugarcane straw; Trace-gases; Tropospheric ozone; Unburned hydrocarbons; Air quality; Cobalt; Environmental impact; Ethanol; Greenhouse gases; Harvesting; Carbon dioxide; atmospheric pollution; burning; emission; environmental factor; greenhouse gas; laboratory method; ozone; particulate matter; troposphere